2015
DOI: 10.1016/j.jbiomech.2015.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of low-modulus and standard acrylic bone cements in simulated vertebroplasty: A human ex vivo study

Abstract: The high stiffness of bone cements used in vertebroplasty has been hypothesized to contribute to the propensity of adjacent vertebral fractures after treatment. Therefore, new lowmodulus cements have been developed; however, there are currently no studies assessing the biomechanical aspects of vertebroplasty with these cements in an ex vivo non-prophylactic model. In this study, we induced wedge fractures through eccentric uniaxial compression to single wholevertebrae, before and after augmentation with either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…It was injectable for more than 15 min and exhibited both high flexibility and a screw holding power similar to CaP cement. Similar formulations (LA-modified PMMA cements) have previously shown reinforcement of the vertebral body in an ex vivo study [26], and been found to give an adequate biological response in both in vitro and in vivo scenarios. [44,47].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…It was injectable for more than 15 min and exhibited both high flexibility and a screw holding power similar to CaP cement. Similar formulations (LA-modified PMMA cements) have previously shown reinforcement of the vertebral body in an ex vivo study [26], and been found to give an adequate biological response in both in vitro and in vivo scenarios. [44,47].…”
Section: Discussionmentioning
confidence: 81%
“…In fact, it has been suggested that vertebral augmentation with stiff PMMA bone cement may facilitate additional osteoporotic fractures in the vicinity of the treated vertebrae [20][21][22][23]. Although additional fractures are likely to appear due to the natural course of osteoporosis, the disproportionally high number of new fractures occurring next to the treated vertebrae [24,25] suggest that the high cement stiffness [26][27][28][29], and/or high volume fill [29][30][31] may facilitate new fractures. Indeed, ex vivo and finite element studies have reported an increase of the overall vertebral body stiffness of 13% to 33% due to the injection of PMMA bone cement [26,27,32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimizing the modulus of PMMA could prove to be useful in this case. Low-modulus PMMA was previously proposed for spinal applications (López et al, 2011(López et al, , 2014Holub et al, 2015;Persson et al, 2015) and could be beneficial in PCD, particularly for osteoporotic patients. This method could also serve as a screening phase where different surgical advancements can be evaluated without putting patients at risk.…”
Section: Figure 12mentioning
confidence: 99%
“…The values of each component before and after immersion ranged from 0.43 ± 0.11 to1.17 ± 0.96 GPa, and the decreased elastic modulus compared to PMMA bone cement could effectively reduce the risk of fractures in the adjacent vertebrae of osteoporotic bone. 40,41,25 The improved mechanical properties of the DMBC were mainly due to the high mechanical properties of the lamellar GO, 42,43 which interacted with the molecular chain in the bulk, thus leading to the internal threedimensional network structure more stable. While P(MMA-AA)-GO preserved the unique two-dimensional lamellar structure of GO, and its large specific surface area provided more geometric constraints for the flow of P(MMA-AA) molecular chains in the bone cement.…”
Section: Mechanical Propertiesmentioning
confidence: 99%